2015
DOI: 10.1039/c5cp02591e
|View full text |Cite
|
Sign up to set email alerts
|

In situ site-selective transition metal K-edge XAS: a powerful probe of the transformation of mixed-valence compounds

Abstract: We present herein the first in situ site-selective XAS experiment performed on a proof-of-principle transformation of a mixed-valence compound: the calcination of the K0.1Co(II)4[Co(III)(CN)6]2.7·20H2O Prussian Blue analogue (containing Co(2+) and Co(3+) ions in two different Oh sites) into Co3O4 (containing Co(2+) ions in a Td site and Co(3+) in an Oh site). By recording the Co K-edge X-ray absorption spectra using a spectrometer aligned at the Co Kβ1,3 emission line, the evolution of each species was singly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Principle of X‐ray absorption spectroscopy (XAS)‐fluorescence measurement using solid‐state detector (SSD) and crystal analyzer spectrometer (CAS). Spectra correspond to the analysis of a Co 3 O 4 sample with a 30‐element Ge SSD (total fluorescence yield, red spectra) and a CAS using five Ge(444) crystals optimized around the Co K β 1,3 fluorescence line (high‐energy resolution fluorescence detected [HERFD], blue spectra; Bordage et al, 2015). (a) XAS spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Principle of X‐ray absorption spectroscopy (XAS)‐fluorescence measurement using solid‐state detector (SSD) and crystal analyzer spectrometer (CAS). Spectra correspond to the analysis of a Co 3 O 4 sample with a 30‐element Ge SSD (total fluorescence yield, red spectra) and a CAS using five Ge(444) crystals optimized around the Co K β 1,3 fluorescence line (high‐energy resolution fluorescence detected [HERFD], blue spectra; Bordage et al, 2015). (a) XAS spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the selected transitions, XES is divided into two main regions: core‐to‐core (e.g., K α1,2 or K β1,3 ) and valence‐to‐core (e.g., K β2,5 ). In the example of K emission lines of 3d transition metals, core‐to‐core XES permits the evolution of the local spin or oxidation state to be followed and may be used in turn to collect oxidation state‐selective EXAFS (Glatzel et al, 2002) or XANES (Bordage et al, 2015). In addition, valence‐to‐core XES is more sensitive to metal‐ligand mixed valence states and has been employed in chemistry to distinguish between ligands of light elements (Eeckhout et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Red triangles represent the cation in tetrahedral environments, the full and empty symbols correspond to the QHA and TEO (thermal expansion only) calculations, respectively. The dashed lines are the best fits using eqn (11). Saturation temperatures, T s , are given in ESI.…”
Section: Sensitivity To the Local Environmentmentioning
confidence: 99%
“…[3][4][5] Moreover, recent breakthroughs in methodology and instrumentation provide a qualitative enhancement of experimental data. [6][7][8][9][10][11] However, the use of accurate and appropriate theoretical tools is mandatory to fully interpret experiments. [12][13][14][15][16] Most state-of-the-art simulation methods neglect nuclear degrees of freedom by assuming that atoms are fixed at their equilibrium positions.…”
Section: Introductionmentioning
confidence: 99%
“…To extract the cation site-occupation, we employ the K β XES because of its sensitivity to the oxidation state, spin state, and ligand geometry of the cations. [12,23,24] We have shown that XES is more accurate than conventional techniques such as X-ray absorption spectroscopy. [12,19] The site-occupation of Mn x Fe 3−x O 4 can be summarized as x O 4 films have partially inverse spinel structure, where the degree of inversion "i" is defined as the fraction of M 3+ cations at T d sites (where M = Fe, Mn).…”
mentioning
confidence: 99%